WATER ABSORPTION AND WATER RESISTANCE OF THE WATERPROOFING MATERIAL GIDROIZOL-K (Scientific journal of the Fergana State University, 2025)
The waterproofing material Gidroizol-K is tested according to two standard requirements: water absorption and water resistance of the material. The results of testing the samples of the Gidroizol-K waterproofing material are presented. A graph of water absorption for Gidroizol-K waterproofing material samples with thicknesses of 3 mm, 5 mm, and 10 mm was constructed. It was proven that the sample of Gidroizol-K waterproofing material with a thickness of 5 mm has the best water absorption rate of 0.59% compared to the other samples. According to GOST 8625-77, based on the obtained test results, the water resistance of the Gidroizol-K waterproofing material samples was determined by the absence of water traces on the surface of the three samples. In the future, each sample of the Gidroizol-K roofing material will undergo tests such as compression under load, dropping the material for a certain time until fragments are formed, and rotating the material until fragments are formed.